Syndrome of Inappropriate Antidiuretic Hormone (Siadh) in Lung Cancer - Andayani, Novita; Husna, Cut Asmaul (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2023)
Lung cancer is one of the deadliest cancers in both men and women. Lung cancer is generally divided into 2, categories: small-cell lung carcinoma and non-small-cell lung carcinoma. Small cell lung carcinoma (SCLC) represents approximately 15% of all lung cancers. Paraneoplastic syndromes occur in 10% of lung cancer cases and constitute a group of disorders associated with the secretion of functional polypeptides or hormones from tumor cells. The syndrome of inappropriate antidiuretic hormone is a paraneoplastic syndrome that is closely related to SCLC and is associated with worse survival. The key to understanding SIADH is that the hyponatremia that occurs in this syndrome is not caused by Na+ deficiency but rather by excess fluid. The syndrome of inappropriate antidiuretic hormone that occurs is a secondary event caused by the release of antidiuretic hormone due to tumor lysis or because the tumor releases ectopic ADH. Hyponatremia in SCLC is a negative prognostic factor in hospitalized patients and patients with advanced disease